2018
DOI: 10.1128/jvi.00090-18
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Nanotubes as a Novel Route of Cell-to-Cell Spread of Herpesviruses

Abstract: Various types of intercellular connections that are essential for communication between cells are often utilized by pathogens. Recently, a new type of cellular connection, consisting of long, thin, actin-rich membrane extensions named tunneling nanotubes (TNTs), has been shown to play an important role in cell-to-cell spread of HIV and influenza virus. In the present report, we show that TNTs are frequently formed by cells infected by an alphaherpesvirus, bovine herpesvirus 1 (BoHV-1). Viral proteins, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 56 publications
(61 reference statements)
1
81
0
1
Order By: Relevance
“…5. Alternatively, some studies have suggested that subviral components may be transferred directly to adjacent cells through transient pores or other intercellular connection mechanisms, such as tunneling nanaotubes (45, 76, 77). Overall, specific infectivity of virions might have a dramatic effect on the efficiency of the cell-free route (2a-4a) where the virus is subject to physical limitations related to diffusion and to inactivation by neutralizing antibodies, complement components, and other host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…5. Alternatively, some studies have suggested that subviral components may be transferred directly to adjacent cells through transient pores or other intercellular connection mechanisms, such as tunneling nanaotubes (45, 76, 77). Overall, specific infectivity of virions might have a dramatic effect on the efficiency of the cell-free route (2a-4a) where the virus is subject to physical limitations related to diffusion and to inactivation by neutralizing antibodies, complement components, and other host defenses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oAβ is implicated in PAK1 dependent synaptic dysfunctions and PAK1 is aberrantly activated and translocated from the cytosol to the membrane during the development of pathology in the AD brain . Interestingly, HIV and HSV viruses exploit PAK1 kinase dependent macropinocytosis en route and recent studies have also shown direct cell-to-cell spreading of HIV and HSV virus via TNTs Panasiuk et al, 2018). Interesting another report has shown that HIV-1 Nef protein mediated TNT formation associated with 5 proteins of exocyst complex and they involve in a PAK2 and Rab 11 dependent pathway (Mukerji et al, 2012).…”
Section: Oaβ Propagation To Healthy Cells Is Mediated By Transport Inmentioning
confidence: 99%
“…TNTs are defined as thin (50‐200 nm), fragile, and dynamic structures, consisting of plasma membrane and filamentous (F)‐actin . They are involved in cell‐to‐cell interaction and intercellular transport of organelles and pathogens such as virus and bacteria . Leukocytes, their leukemic counterparts and bone marrow stromal cells have all been reported to form TNTs in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 They are involved in cell-to-cell interaction and intercellular transport of organelles and pathogens such as virus and bacteria. 16,[18][19][20][21][22][23][24] Leukocytes, their leukemic counterparts and bone marrow stromal cells have all been reported to form TNTs in vitro. [25][26][27][28][29][30][31][32] TNT is proposed to be a mechanism for chemo resistance by transport of oncoproteins between T and B cells as well as in colon cancer cells, by transfer of mitochondria from endothelial cells to chemotherapy exposed cancer cells, or by induced drug-efflux in aggressive forms of pancreatic carcinoma.…”
Section: Introductionmentioning
confidence: 99%